High-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film and preparation method thereof

By uniformly mixing polyvinylpyrrolidone modified carbon nanotubes and aqueous polyamic acid salt in an aqueous solvent and undergoing thermal imidation treatment, a high-performance aqueous polyimide/carbon nanotube composite electromagnetic shielding film was prepared, solving the problem of difficult to take into account both mechanical properties and electromagnetic shielding performance under high conductive fillers, and achieving both high strength, high temperature resistance and high electromagnetic shielding performance.

CN119505317AActive Publication Date: 2025-02-25NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI

Patent Information

Application Number
CN202411746016.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-25
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The prior art is difficult to achieve flexible, high-strength and high-temperature-resistant polyimide composite films under high conductive filler loading, resulting in difficult to take into account both electromagnetic shielding and mechanical properties.

Method used

Using water as a solvent, a high-performance aqueous polyimide/carbon nanotube composite electromagnetic shielding film was prepared by uniformly mixing the polyvinylpyrrolidone-modified carbon nanotube slurry with aqueous polyamic acid salt, combined with thermal imidation treatment.

Benefits of technology

Under extremely high loading of carbon nanotube content (66.7 wt%), the excellent mechanical properties and electromagnetic shielding performance of the composite film are achieved, and are stable under high temperature conditions, with an electromagnetic shielding performance of 51 dB.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505317A_ABST
    Figure CN119505317A_ABST
Patent Text Reader

Abstract

The invention discloses a high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film and a preparation method thereof. The preparation method comprises the following steps: reacting a first mixed reaction system containing a diamine monomer, a salt-forming reagent and a dianhydride monomer to obtain water-based polyamide acid salt; uniformly mixing the polyvinylpyrrolidone modified carbon nanotube aqueous dispersion liquid with the aqueous polyamide acid salt to form an aqueous polyamide acid salt / carbon nanotube dispersion liquid; and applying the water-based polyamide acid salt / carbon nanotube dispersion liquid to a substrate, and then carrying out thermal imidization treatment to prepare the high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film. The preparation method provided by the invention is simple, safe and environment-friendly, and is suitable for industrial popularization and application, and the finally prepared composite film can still maintain good mechanical properties and high-temperature electromagnetic shielding performance under the condition of high carbon nanotube content, and is beneficial to application in extreme environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyimide nanocomposite film preparation, and in particular relates to a high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film and a green preparation method thereof. Background Art

[0002] The rapid development of electronic and communication technologies has put forward higher requirements for electromagnetic shielding materials. Ultra-thin, flexible, high-strength and heat-resistant electromagnetic shielding materials are indispensable in many fields such as aerospace, electronics and small wearable electronic products. Traditional metal materials (Ag, Cu, Fe) are limited by high density and are susceptible to corrosion. More importantly, the electrical properties of metal and alloy nanomaterials decrease with increasing temperature, resulting in a decrease in their electromagnetic wave shielding ability. At the same time, the defects of metal materials such as susceptibility to corrosion, high density and poor flexibility also limit their practical application in specific fields. In addition, magnetic materials such as iron oxide and cobalt oxide can achieve efficient attenuation of electromagnetic waves, but are limited by the Curie temperature, which is not conducive to their use under high temperature conditions.

[0003] It is worth noting that carbon nanotubes have excellent electrical conductivity, high mechanical strength and large-scale production capabilities, showing great potential in the development of electromagnetic shielding materials. The electrical conductivity of a single carbon nanotube is as high as 1×10 8 S / m, mechanical strength exceeds 1×10 5 MPa. The preparation of conductive polymers for electromagnetic shielding by combining with polymers with good processing properties has attracted much attention. However, the performance of traditional carbon nanotube macroscopic films is much lower than that of single carbon nanotubes. The main reason is that the arrangement of carbon nanotubes in the film is loose and disordered, which inhibits the improvement of the performance of carbon nanotube films. Polyimide materials usually show excellent mechanical properties at high and low temperatures (-200 ~ 300 ℃), and have great application potential in the field of electromagnetic shielding materials.

[0004] The good dispersion of fillers in the polymer matrix determines the comprehensive performance of the composite film. Some scholars use polyamic acid and MXene to prepare high-performance conductive composite films. For example, Chinese patent CN752331159A discloses a method of synthesizing polyimide precursor polyamic acid in an organic solvent such as N, N-dimethylacetamide (DMAc), and then reacting with triethylamine and water to prepare a polyamic acid aqueous solution and MXene uniformly mixed, and finally preparing a polyimide / MXene composite film for electromagnetic shielding. However, when the mass of MXene accounts for 60wt% of the total mass of the polyimide composite system, the strength of the composite film has dropped to about 80MPa, and the electromagnetic shielding performance of the composite film is about 28dB.

[0005] However, high content of conductive fillers (>30wt%) usually leads to a sharp decrease in the mechanical properties of the polymer matrix while giving the polymer good conductivity. Therefore, it is of great significance to prepare flexible, high-strength and high-temperature resistant polyimide composite films with high conductive fillers for electromagnetic shielding in harsh environments. Summary of the invention

[0006] The main purpose of the present invention is to provide a high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film and an green preparation method thereof, so as to overcome the shortcomings of the prior art.

[0007] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:

[0008] The embodiment of the present invention provides a method for preparing a high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film, which comprises:

[0009] reacting a first mixed reaction system comprising a diamine monomer, a salt-forming agent and a dianhydride monomer to obtain an aqueous polyamic acid salt;

[0010] The polyvinyl pyrrolidone-modified carbon nanotube aqueous dispersion and aqueous polyamic acid salt are uniformly mixed to form an aqueous polyamic acid salt / carbon nanotube dispersion;

[0011] The aqueous polyamic acid salt / carbon nanotube dispersion is applied to a substrate, and then subjected to thermal imidization treatment to obtain a high-performance aqueous polyimide / carbon nanotube composite electromagnetic shielding film.

[0012] In some embodiments, the process conditions of the thermal imidization treatment include: heating treatment at a gradient temperature of 100 to 450° C. for 0.5 to 2 h under nitrogen or vacuum conditions.

[0013] In some embodiments, the preparation method comprises:

[0014] Casting the aqueous polyamic acid salt / carbon nanotube dispersion on a substrate, and heating to remove the solvent to obtain an aqueous polyamic acid salt / carbon nanotube composite film;

[0015] The water-based polyamic acid salt / carbon nanotube composite film is heated to complete thermal imidization treatment and remove polyvinyl pyrrolidone to obtain a high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film.

[0016] Furthermore, an embodiment of the present invention also provides a high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film prepared by the aforementioned preparation method.

[0017] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0018] 1) The entire preparation process provided by the present invention uses water as a solvent, thereby avoiding the use of a large amount of organic solvents. The preparation method is simple and environmentally friendly, and is suitable for industrial promotion;

[0019] 2) The polyvinyl pyrrolidone-modified carbon nanotube slurry used in the present invention exhibits excellent compatibility with the polyimide precursor polyamic acid salt aqueous solution, avoiding the problem of mechanical property degradation caused by agglomeration of conductive fillers, and achieving excellent mechanical properties and electromagnetic shielding properties under extremely high carbon nanotube content loading (66.7wt%);

[0020] 3) The aqueous polyimide / carbon nanotube composite electromagnetic shielding film finally prepared by the present invention exhibits excellent mechanical properties (tensile strength is about 68-284MPa) and an electromagnetic shielding effectiveness of up to about 51dB, and remains stable under high temperature conditions (350°C), and even improves the electromagnetic shielding effectiveness by 1.5dB compared to room temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still belong to the scope of the present invention.

[0022] Figure 1 is the H-NMR spectrum of the aqueous polyamic acid salt obtained in Example 1 of the present invention;

[0023] Figure 2 The particle size distribution diagram of the aqueous polyamic acid salt / PVP / CNT dispersion obtained in Examples 1, 2, 3, and 4 of the present invention;

[0024] Figure 3 This is a cross-sectional scanning electron microscope image of the high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film obtained in Example 2 of the present invention;

[0025] Figure 4 Graphs showing stress-strain curves of high-performance waterborne polyimide / carbon nanotube composite electromagnetic shielding films obtained in Examples 1, 2, 3, 4, 5, and 6 of the present invention;

[0026] Figure 5 This is a scatter plot of the X-band electromagnetic shielding effectiveness of the high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0027] Traditional conductive polymer composites as electromagnetic shielding materials often require high conductive filler loading to achieve high electromagnetic shielding effectiveness, but high filler content often leads to agglomeration and other phenomena, resulting in a sharp decline in mechanical properties. After long-term research and extensive practice, the inventors of this case aim to solve the balance between the mechanical properties and electromagnetic shielding properties of composite materials at high filler content, and achieve comprehensive performance improvements to meet the needs of practical applications.

[0028] The present invention synthesizes a series of water-based polyimides. What is exciting is that the carbon nanotube slurry modified by polyvinyl pyrrolidone shows excellent compatibility with the polyimide precursor polyamic acid salt aqueous solution, especially the cation-π interaction and electrostatic interaction between the water-based polyamic acid salt based on the imidazole salt series and the carbon nanotubes, which is conducive to the stability of the mixed dispersion, avoids the problems of mechanical property degradation caused by the agglomeration of conductive fillers, and finally realizes the high content loading of carbon nanotubes (66.7wt%). The finally prepared water-based polyimide / carbon nanotube composite film shows excellent mechanical properties and electromagnetic shielding properties.

[0029] The technical solution, its implementation process and principle will be further explained as follows.

[0030] An aspect of an embodiment of the present invention provides a method for preparing a high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film (also referred to as a "water-based polyimide (WPI)-based flexible electromagnetic shielding composite film"), comprising:

[0031] reacting a first mixed reaction system comprising a diamine monomer, a salt-forming agent and a dianhydride monomer to obtain an aqueous polyamic acid salt;

[0032] The polyvinyl pyrrolidone-modified carbon nanotube aqueous dispersion and aqueous polyamic acid salt are uniformly mixed to form an aqueous polyamic acid salt / carbon nanotube dispersion;

[0033] The aqueous polyamic acid salt / carbon nanotube dispersion is applied to a substrate, and then subjected to thermal imidization treatment to obtain a high-performance aqueous polyimide / carbon nanotube composite electromagnetic shielding film.

[0034] In some embodiments, the diamine monomer may include (p-phenylenediamine), (4,4′-diaminodiphenyl ether), (2,2-dimethylbenzidine) or a combination of two or more thereof, but not limited thereto.

[0035] In some embodiments, the dianhydride monomer is (3,3',4,4-biphenyltetracarboxylic dianhydride).

[0036] In some embodiments, the salt-forming agent is a basic salt-forming agent, for example, preferably (Triethylamine), (1,2-dimethylimidazole), (imidazole), etc., or a combination of two or more thereof, but not limited thereto.

[0037] In some embodiments, the molar ratio of the diamine monomer to the dianhydride monomer is 0.98:1 to 1:1.

[0038] In some embodiments, the molar ratio of the dianhydride monomer to the salt-forming agent is 1:2 to 1:5.

[0039] In some embodiments, the preparation method includes: mixing a diamine monomer and deoxygenated water, adding a salt-forming agent to assist the rapid dissolution of the diamine monomer, then adding a dianhydride monomer, stirring and mixing evenly, and reacting to obtain an aqueous polyamic acid salt solution.

[0040] Furthermore, the stirring speed is controlled at 100-300 rpm.

[0041] Furthermore, the ratio of the diamine monomer to water is (0.01-0.05) mol: (50-200) mL.

[0042] Furthermore, the viscosity of the aqueous polyamic acid salt solution is 40,000 to 100,000 cP.

[0043] In some embodiments, the reaction is carried out under a protective atmosphere (such as a nitrogen atmosphere), the reaction temperature is set at 25 to 80° C., and the reaction time is 6 to 12 hours.

[0044] In some embodiments, the preparation method includes: modifying carbon nanotubes with polyvinyl pyrrolidone to obtain a polyvinyl pyrrolidone-modified carbon nanotube aqueous dispersion.

[0045] In some embodiments, the preparation method comprises: mixing a polyvinyl pyrrolidone-modified carbon nanotube aqueous dispersion and an aqueous polyamic acid salt, and ultrasonicating and stirring to obtain a uniformly mixed aqueous polyamic acid salt / carbon nanotube dispersion.

[0046] Furthermore, the diameter of the carbon nanotubes is 5 to 50 nm.

[0047] In some more preferred embodiments, the mass ratio of polyvinyl pyrrolidone to carbon nanotubes is 1:4 to 1:9.

[0048] In some more preferred embodiments, the carbon nanotube aqueous dispersion is modified by polyvinyl pyrrolidone, and the mass ratio of the aqueous polyamic acid salt to the carbon nanotubes is 10:1 to 1:5.

[0049] In some more preferred embodiments, the solid content of the aqueous polyamic acid salt / carbon nanotube dispersion is 20 to 60 mg / mL, preferably 20 to 50 mg / mL.

[0050] In some more preferred embodiments, the ultrasonic temperature is 20-30° C., the ultrasonic time is 0.5-2 h, and the ultrasonic power is 100-500 kHz.

[0051] In some more preferred embodiments, the stirring speed is 300-600 rpm, and the stirring time is 12-36 h.

[0052] In some embodiments, the preparation method specifically comprises:

[0053] Casting the aqueous polyamic acid salt / carbon nanotube dispersion on a substrate, and heating to remove the solvent to obtain an aqueous polyamic acid salt / carbon nanotube composite film;

[0054] The water-based polyamic acid salt / carbon nanotube composite film is heated to complete thermal imidization treatment and remove polyvinyl pyrrolidone to obtain a high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film.

[0055] Furthermore, the heating temperature is 50-80° C. and the heating time is 1-3 hours.

[0056] Further, the substrate includes a glass plate, but is not limited thereto.

[0057] In some embodiments, the process conditions for thermal imidization treatment of the waterborne polyimide / carbon nanotube composite film include: heating treatment at a gradient temperature of 100 to 450° C. for 0.5 to 2 h under nitrogen or vacuum conditions.

[0058] In some more preferred embodiments, the thermal imidization treatment of the water-based polyimide / carbon nanotube composite film is: gradient temperature treatment under nitrogen protection, the specific procedure is: first heat to 100-120°C and keep for 1-2h, heat to 150-170°C and keep for 1-2h, heat to 200-220°C and keep for 1-2h, heat to 250-270°C and keep for 1-2h, heat to 300-320°C and keep for 0.5-2h, and finally heat to 350-450°C and heat to dehydrate the polyamic acid to form an imide ring, and perform cyclization treatment for 0.5-2h.

[0059] In some specific embodiments, the preparation method of the high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film mainly includes:

[0060] In a green water solvent, 4,4′-diaminodiphenyl ether (ODA), p-phenylenediamine (PDA) and the like are used as diamines, 3,3′,4,4-biphenyltetracarboxylic dianhydride (BPDA) and the like are used as dianhydrides, and 1,2-dimethylimidazole (DMZ), triethylamine (TEA) or imidazole (IM) are used as salt-forming agents to initiate the preparation of water-based polyamic acid salts (WPAAS). The obtained water-based polyamic acid salts are uniformly mixed with the water-based slurry of multi-walled carbon nanotubes (MWCNTs). Due to the existence of hydrogen bonds, cation-π, π-π interactions between the polyamic acid salts and the water-based slurry of carbon nanotubes, the mixed solution system exhibits excellent dispersibility. Finally, a water-based polyimide / carbon nanotube composite electromagnetic shielding film with high strength and high electromagnetic shielding performance is prepared by simple solution casting and thermal imidization treatment.

[0061] In some more specific embodiments, the method for preparing the high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film comprises the following steps:

[0062] (1) adding a diamine monomer and deionized water to a three-necked flask, adding an alkaline salt-forming agent to assist the rapid dissolution of the diamine monomer, and then adding a dianhydride monomer to react to obtain an aqueous polyamic acid salt solution;

[0063] (2) mixing the aqueous dispersion of multi-walled carbon nanotubes modified with polyvinyl pyrrolidone (PVP) and the aqueous polyamic acid salt solution obtained in step (1), ultrasonicating and stirring, to obtain a uniformly mixed aqueous polyamic acid salt / carbon nanotube dispersion;

[0064] (3) pouring the aqueous polyamic acid salt / carbon nanotube dispersion obtained in step (2) onto a clean glass plate of 5×10 cm, and heating it in an oven to remove the solvent water to obtain an aqueous polyamic acid salt / carbon nanotube composite film;

[0065] (4) The obtained polyamic acid salt / carbon nanotube composite film is heated to 350-450° C. in an oven to complete thermal imidization and remove polyvinyl pyrrolidone, thereby finally obtaining a high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film.

[0066] Furthermore, in step (2), the ultrasonic continuous temperature of the aqueous polyamic acid salt / carbon nanotube dispersion is 20-30° C., the ultrasonic time is 0.5-2 h, the ultrasonic power is 100-500 kHz, the stirring speed is 300-600 rpm, and the stirring time is 12-36 h.

[0067] Furthermore, in step (3), the treatment temperature of the aqueous polyamic acid salt / carbon nanotube composite film in the oven is 50 to 80° C. and the treatment time is 1 to 3 hours.

[0068] Among them, in some more preferred embodiments, a method for preparing a high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film specifically comprises the following steps:

[0069] (1) In a deoxygenated aqueous solvent, a diamine monomer and a salt-forming agent are added to assist in dissolution to obtain a completely dissolved diamine monomer solution, and then a dianhydride monomer is added to react with the diamine monomer to obtain a high-viscosity aqueous polyamic acid salt solution (40000-100000 cP). The molar ratio of the diamine monomer to the dianhydride monomer is 0.98:1-1:1, the molar ratio of the dianhydride monomer to the alkaline salt-forming agent is 1:2-1:5, and the ratio of the diamine monomer to the solvent is (0.01-0.05) mol: (50-200) mL.

[0070] (2) The aqueous polyamic acid salt solution obtained in step (1) is mixed with the aqueous slurry of carbon nanotubes modified by polyvinyl pyrrolidone, and uniformly dispersed by ultrasound and stirring. The aqueous polyamic acid salt / carbon nanotube dispersion is poured onto a clean glass plate and heated in an oven to remove the solvent water to obtain an aqueous polyamic acid salt / carbon nanotube composite film. The mass ratio of polyvinyl pyrrolidone to carbon nanotubes is determined to be 1:9 to 1:4. The mass ratio of aqueous polyamic acid salt to carbon nanotubes is 10:1 to 1:5, and the solid content of the aqueous polyamic acid salt / carbon nanotube dispersion is 20 to 50 mg / ml.

[0071] (3) The polyamic acid salt / carbon nanotube film obtained in step (2) is subjected to a thermal imidization treatment in an oven at a gradient temperature of 100 to 450° C. for 0.5 to 2 h to obtain a high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film.

[0072] Furthermore, the preparation processes of steps (1) and (2) are both carried out using deionized water as the solvent, thus avoiding the use of large amounts of organic solvents. The entire preparation process is simple, safe, and environmentally friendly, and is suitable for industrial promotion.

[0073] In summary, the present invention uses water as a solvent, avoiding the use of a large amount of organic solvents. The preparation method is simple and environmentally friendly, suitable for industrial promotion, and has important significance for the scientific research and practical application of polyimide-based composite electromagnetic shielding materials. The polyvinyl pyrrolidone-modified carbon nanotube slurry shows excellent compatibility with the polyimide precursor polyamic acid salt aqueous solution, avoiding the problems of mechanical property degradation caused by the agglomeration of conductive fillers, and achieving extremely high carbon nanotube content loading (66.7wt%).

[0074] Another aspect of the embodiments of the present invention further provides a high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film prepared by the aforementioned preparation method, wherein the film achieves an extremely high carbon nanotube content loading (66.7 wt %).

[0075] Furthermore, the high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film has a thickness of 20 to 350 μm, a tensile strength of 68 to 284 MPa, and an electromagnetic shielding effectiveness of up to 51 dB.

[0076] Furthermore, the high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film prepared by the present invention exhibits excellent mechanical properties (tensile strength of about 68-284MPa) and electromagnetic shielding effectiveness up to 51dB. More importantly, the electromagnetic shielding performance of the high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film remains stable under high temperature conditions (350°C), and even improves the electromagnetic shielding effectiveness by 1.5dB compared to that at room temperature.

[0077] In summary, the composite film finally prepared by the present invention can still maintain good mechanical properties and high-temperature electromagnetic shielding properties at a high carbon nanotube content, which is conducive to its application in extreme environments.

[0078] In order to further understand the present invention, the water-based polyimide / carbon nanotube composite electromagnetic shielding film provided by the present invention will be described in detail in combination with the embodiments below. In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention can also be implemented in other ways different from those described herein, and those skilled in the art can make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0079] Unless otherwise specified, the raw materials and reagents in the examples of the present invention were purchased from commercial sources.

[0080] The polyvinyl pyrrolidone-modified carbon nanotube aqueous dispersion used in the following examples is prepared by modifying carbon nanotubes with polyvinyl pyrrolidone, specifically comprising: mixing the polyvinyl pyrrolidone-modified carbon nanotube aqueous dispersion with aqueous polyamic acid salt, ultrasonicating, and stirring to obtain a uniformly mixed aqueous polyamic acid salt / carbon nanotube dispersion. The diameter of the carbon nanotube is 5 to 50 μm, and the mass ratio of the polyvinyl pyrrolidone to the carbon nanotube is 1:4 to 1:9.

[0081] Example 1

[0082] (1) First, weigh about 150 mL of deionized water and add it to a 250 mL three-necked flask. Under nitrogen flow, heat it to 80° C. to remove oxygen from the deionized water and set it aside.

[0083] (2) At room temperature and nitrogen, p-phenylenediamine (3.0279 g, 0.028 mol) and 1,2-dimethylimidazole (6.3 mL, 0.07 mol) were added to 101 mL of the above deionized water and reacted for 0.5 h until the p-phenylenediamine monomer was completely dissolved. Then, dianhydride monomer 3,3′,4,4′-biphenyltetracarboxylic dianhydride (8.2376 g, 0.028 mol) was added, and the temperature was raised to 70° C. and reacted for 12 h to obtain a high-viscosity polyamic acid salt aqueous solution.

[0084] (3) Add the polyamic acid salt aqueous solution (2.00 g, 5 wt%) obtained in step (2) and the polyvinyl pyrrolidone-modified carbon nanotube slurry (4.00 g, 5 wt%) (the mass ratio of polyvinyl pyrrolidone to carbon nanotubes is 1:5) to 4.00 g of deionized water, ultrasonicate, stir, and prepare a uniform mixed dispersion with a solid content of 3 wt%, and the average particle size of the dispersion is 224 nm. The ultrasonic temperature is 25°C, the ultrasonic time is 1 h, and the ultrasonic power is 300 kHz. The stirring speed is 500 rpm, and the stirring time is 24 h. The above dispersion is poured onto a glass plate with a size of 5x10 cm. Finally, heat-treat in an oven at 50°C, 60°C, 70°C, and 80°C for 2 h, 2 h, 2 h, and 2 h, respectively, to obtain a polyamic acid salt / carbon nanotube composite film.

[0085] (4) The polyamic acid salt / carbon nanotube composite film obtained in the above step (3) is treated at 100°C, 150°C, 200°C, 250°C, 300°C, and 350°C for 1h, 1h, 1h, 1h, 0.5h, and 0.5h, respectively, to obtain a high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film.

[0086] The high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film prepared in this embodiment still maintains excellent mechanical properties when the carbon nanotube content is 66.7wt%, the tensile strength can reach about 174MPa, the modulus can reach about 6.8GPa, the composite film thickness is in the range of 0.02 to 0.35mm, and the corresponding electromagnetic shielding performance can reach 23 to 51dB, which can meet the needs of commercial applications (>20dB). And the composite electromagnetic shielding film can maintain stable electromagnetic shielding performance under high temperature conditions.

[0087] Figure 1 is the H NMR spectrum of the 1,2-dimethylimidazolium salt-terminated polyamic acid salt prepared in this example, Figure 1 It can be seen that the corresponding polyimide precursor salt solution was synthesized. The particle size distribution of the aqueous polyamic acid salt / PVP / CNT dispersion is as follows Figure 2 shown.

[0088] Figure 4This is a stress-strain curve of the high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film prepared in this example.

[0089] Figure 5 The electromagnetic shielding performance of the high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film prepared in this embodiment at 8.2-12.4 GHz (X-band) is that when the film thickness increases from 0.02 mm to 0.35 mm, the electromagnetic shielding effectiveness increases from 23 dB to 51 dB.

[0090] Example 2

[0091] (1) The process is the same as step (1) in Example 1.

[0092] (2) The process is the same as step (2) in Example 1.

[0093] (3) Add the polyamic acid salt aqueous solution (2.00 g, 5 wt%) obtained in step (2) and the polyvinyl pyrrolidone-modified carbon nanotube slurry (2.00 g, 5 wt%) to 2.67 g of deionized water to prepare a uniform mixed dispersion with a solid content of 3 wt%, and an average particle size of the dispersion is 211 nm. The above dispersion is poured onto a glass plate with a size of 5 x 10 cm. Finally, heat-treat in an oven at 50° C., 60° C., 70° C., and 80° C. for 2 h, 2 h, 2 h, and 2 h, respectively, to obtain an aqueous polyamic acid salt / carbon nanotube composite film.

[0094] (4) The process is the same as step (4) in Example 1.

[0095] The high-performance waterborne polyimide / carbon nanotube composite electromagnetic shielding film prepared in this embodiment still maintains excellent mechanical properties when the carbon nanotube content is 50wt%, and the tensile strength can reach 212MPa. The corresponding electromagnetic shielding performance can reach up to 26.3dB when the film thickness is 0.03mm. Moreover, the composite film can maintain stable electromagnetic shielding performance under high temperature conditions of 350℃, and the electromagnetic shielding effectiveness increases to 27.8dB.

[0096] The particle size distribution of the aqueous polyamic acid salt / PVP / CNT dispersion prepared in this example is as follows Figure 2 shown.

[0097] Figure 3 This is a cross-sectional scanning electron microscope of the high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film prepared in this example. Figure 3 It shows that the carbon nanotubes are evenly dispersed in the polymer matrix without obvious agglomeration, which also makes the composite electromagnetic shielding film exhibit excellent mechanical properties.

[0098] Figure 4This is a stress-strain curve of the high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film prepared in this example.

[0099] Example 3

[0100] (1) The process is the same as step (1) in Example 1.

[0101] (2) The process is the same as step (2) in Example 1.

[0102] (3) The polyamic acid salt aqueous solution (4.00 g, 5 wt%) obtained in step (2) and the polyvinyl pyrrolidone-modified carbon nanotube slurry (0.40 g, 5 wt%) were added to 2.93 g of deionized water to prepare a uniform mixed dispersion with a solid content of 3 wt%, and the average particle size of the dispersion was 249 nm. The above dispersion was cast on a glass plate with a size of 5 x 10 cm. Finally, the dispersion was heat-treated in an oven at 50 ° C, 60 ° C, 70 ° C, and 80 ° C for 2 h, 2 h, 2 h, and 2 h, respectively, to obtain an aqueous polyamic acid salt / carbon nanotube composite film.

[0103] (4) The process is the same as step (4) in Example 1.

[0104] The high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film prepared in this embodiment has excellent mechanical properties when the carbon nanotube content is 9.1wt%, and the tensile strength can reach 284MPa. When the film thickness is 0.03mm, the corresponding electromagnetic shielding performance can reach up to 4.3dB.

[0105] Example 4

[0106] (1) The process is the same as step (1) in Example 1.

[0107] (2) The process is the same as step (2) in Example 1.

[0108] (3) Add the polyamic acid salt aqueous solution (2.00 g, 5 wt%) obtained in step (2) and the polyvinyl pyrrolidone-modified carbon nanotube slurry (10.00 g, 5 wt%) to 8.00 g of deionized water to prepare a uniform mixed dispersion with a solid content of 3 wt%, and an average particle size of the dispersion of 370 nm. The above dispersion was cast on a glass plate with a size of 5 x 10 cm. Finally, heat-treated in an oven at 50 ° C, 60 ° C, 70 ° C, and 80 ° C for 2 h, 2 h, 2 h, and 2 h, respectively, to obtain an aqueous polyamic acid salt / carbon nanotube composite film.

[0109] (4) The process is the same as step (4) in Example 1.

[0110] The high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film prepared in this embodiment has a tensile strength of about 68 MPa when the carbon nanotube content is 83.3 wt %, and the corresponding electromagnetic shielding performance can reach up to 36.1 dB when the film thickness is 0.032 mm.

[0111] Example 5

[0112] (1) The process is the same as step (1) in Example 1.

[0113] (2) At room temperature and nitrogen, 4,4′-diaminodiphenyl ether (5.6066 g, 0.028 mol) and 1,2-dimethylimidazole (6.3 ml, 0.07 mol) were added to 124 ml of the above deionized water and reacted for 0.5 h until 4,4′-diaminodiphenyl ether was completely dissolved. Then, dianhydride monomer 3,3′,4,4′-biphenyltetracarboxylic dianhydride (8.2376 g, 0.028 mol) was added, and the temperature was raised to 70° C. and reacted for 12 h to obtain a high-viscosity polyamic acid salt aqueous solution.

[0114] (3) The process is consistent with step (3) in Example 2.

[0115] (4) The process is the same as step (4) in Example 1.

[0116] The high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film prepared in this embodiment has a tensile strength of 126MPa when the carbon nanotube content is 50wt%, while the tensile strength of the pure water-based polyimide film is 134MPa, which is only about 6.0% lower. At the same time, the electromagnetic shielding effectiveness can reach 33dB when the film thickness is about 0.035mm.

[0117] Figure 3 This is the stress-strain curve of the high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film prepared in this embodiment. It can be found that when the carbon nanotube content is greater than 50wt%, the high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film still exhibits excellent mechanical properties.

[0118] Example 6

[0119] (1) The process is the same as step (1) in Example 1.

[0120] (2) At room temperature and nitrogen, p-phenylenediamine (3.0279 g, 0.028 mol) and triethylamine (19.5 ml, 0.14 mol) were added to 101 ml of the above deionized water and reacted for 0.5 h until the p-phenylenediamine monomer was completely dissolved. Then, dianhydride monomer 3,3′,4,4′-biphenyltetracarboxylic dianhydride (8.2376 g, 0.028 mol) was added, and the temperature was raised to 25° C. to react for 12 h to obtain a high-viscosity polyamic acid salt aqueous solution.

[0121] (3) The polyamic acid salt aqueous solution (4.00 g, 5 wt%) obtained in step (2) and the polyvinyl pyrrolidone-modified carbon nanotube slurry (2.00 g, 5 wt%) (the ratio of polyvinyl pyrrolidone to carbon nanotubes is 1:4) are added to 4.00 g of deionized water to prepare a uniform mixed dispersion with a solid content of 3 wt%, and the above dispersion is cast on a glass plate with a size of 5 x 10 cm. Finally, heat treatment is carried out in an oven at 50° C., 60° C., 70° C., and 80° C. for 2 h, 2 h, 2 h, and 2 h, respectively, to obtain an aqueous polyamic acid salt / carbon nanotube composite film.

[0122] (4) The process is the same as step (4) in Example 1.

[0123] The high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film prepared in this embodiment can achieve a tensile strength of 169 MPa when the mass proportion of carbon nanotubes is 33.3 wt %, and the electromagnetic shielding effectiveness can reach 22 dB when the film thickness is about 0.035 mm.

[0124] Example 7

[0125] (1) The process is the same as step (1) in Example 1.

[0126] (2) At room temperature and nitrogen, p-phenylenediamine (3.0279 g, 0.028 mol) and imidazole (4.77 g, 0.07 mol) were added to 101 ml of the above deionized water and reacted for 0.5 h until the p-phenylenediamine monomer was completely dissolved. Then, dianhydride monomer 3,3′,4,4′-biphenyltetracarboxylic dianhydride (8.2376 g, 0.028 mol) was added, and the temperature was raised to 70° C. to react for 12 h to obtain a high-viscosity polyamic acid salt aqueous solution.

[0127] (3) The polyamic acid salt aqueous solution (4.00 g, 5 wt%) obtained in step (2) and the polyvinyl pyrrolidone-modified carbon nanotube slurry (2.00 g, 5 wt%) were added to 4.00 g of deionized water to prepare a uniform mixed dispersion with a solid content of 3 wt%, and the dispersion was cast onto a glass plate with a size of 5 x 10 cm. Finally, the dispersion was heat-treated in an oven at 50° C., 60° C., 70° C., and 80° C. for 2 h, 2 h, 2 h, and 2 h, respectively, to obtain an aqueous polyamic acid salt / carbon nanotube composite film.

[0128] (4) The process is the same as step (4) in Example 1.

[0129] The high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film prepared in this embodiment has an electromagnetic shielding effectiveness of 23 dB when the mass proportion of carbon nanotubes is 33.3 wt % and the film thickness is about 0.03 mm.

[0130] Example 8

[0131] The difference between this embodiment and embodiment 1 is that:

[0132] In step (2), the molar ratio of p-phenylenediamine to 3,3',4,4'-biphenyltetracarboxylic dianhydride is 0.98:1, and the molar ratio of 3,3',4,4'-biphenyltetracarboxylic dianhydride to 1,2-dimethylimidazole is 1:2. The ratio of p-phenylenediamine to deionized water is 0.01 mol:50 mL. The temperature is raised to 60°C for reaction for 10 hours to obtain a high-viscosity polyamic acid salt aqueous solution.

[0133] In step (3), the mass ratio of the aqueous polyamic acid salt to the carbon nanotubes is 10:1. The ultrasonic temperature is 20°C, the ultrasonic time is 2 hours, the ultrasonic power is 100 kHz, the stirring speed is 300 rpm, and the stirring time is 36 hours.

[0134] In step (4), the polyamic acid salt / carbon nanotube composite film is treated at 120°C, 170°C, 220°C, 270°C, 320°C and 450°C for 2h, 2h, 2h, 2h, 2h and 2h, respectively, to obtain a high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film.

[0135] Example 9

[0136] The difference between this embodiment and embodiment 1 is that:

[0137] In step (2), the molar ratio of p-phenylenediamine to 3,3',4,4'-biphenyltetracarboxylic dianhydride is 0.99:1, and the molar ratio of 3,3',4,4'-biphenyltetracarboxylic dianhydride to 1,2-dimethylimidazole is 1:3. The ratio of p-phenylenediamine to deionized water is 0.05 mol:200 mL. The temperature is raised to 80°C and reacted for 6 hours to obtain a high-viscosity polyamic acid salt aqueous solution.

[0138] In step (3), the mass ratio of the aqueous polyamic acid salt to the carbon nanotubes is 1:5. The ultrasonic temperature is 30°C, the ultrasonic time is 0.5h, the ultrasonic power is 500kHz, the stirring speed is 600rpm, and the stirring time is 12h.

[0139] Example 10

[0140] The difference between this embodiment and embodiment 1 is that:

[0141] The polyvinyl pyrrolidone-modified carbon nanotube slurry (4.00 g, 5 wt%) in step (3) is a polyvinyl pyrrolidone-to-carbon nanotube slurry with a mass ratio of 1:9. The uniform mixed dispersion with a solid content of 3 wt% is cast onto a glass plate with a size of 5 x 10 cm. Finally, the mixture is heat-treated in an oven at 50° C., 60° C., 70° C., and 80° C. for 2 h, 2 h, 2 h, and 2 h, respectively, to obtain an aqueous polyamic acid salt / carbon nanotube composite film.

[0142] The high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film prepared in this embodiment has a tensile strength of about 161 MPa when the carbon nanotube content is 66.7 wt%, and the corresponding electromagnetic shielding performance can reach up to 25.8 dB when the film thickness is 0.033 mm, also achieving high tensile strength and electromagnetic shielding effectiveness.

[0143] Comparative Example 1

[0144] CN752331159A discloses a method for synthesizing a polyimide precursor polyamic acid in an organic solvent such as N,N-dimethylacetamide (DMAc), and then reacting with triethylamine and water to prepare a polyamic acid aqueous solution and uniformly mixing it with MXene, and finally preparing a polyimide / MXene composite film for electromagnetic shielding. However, when the mass of MXene accounts for 60wt% of the total mass of the polyimide composite system, the strength of the composite film is only 80MPa, and the elongation at break is <2%. The mechanical properties of the composite film are significantly reduced when the MXene content is high. In addition, the electromagnetic shielding effectiveness of the composite film is about 28dB. It is worth noting that the preparation of the polyamic acid aqueous solution in this method is cumbersome and involves the use of a large amount of organic solvents.

[0145] In the present invention, when the carbon nanotube filler content is equivalent (66.7wt%), the mechanical strength of the waterborne polyimide / carbon nanotube composite film can reach 174MPa, and at the same time, the composite film is endowed with good electromagnetic shielding performance (23-51dB). In addition, the present invention is completely carried out in water solvent, avoiding the use of a large amount of organic solvents, and is suitable for industrial promotion.

[0146] Comparative Example 2

[0147] (1) First, about 55 mL of N-methylpyrrolidone was added to a 100 mL three-necked flask. At room temperature and nitrogen, p-phenylenediamine (2.6494 g, 0.0245 mol) was added to the organic solvent until the p-phenylenediamine monomer was completely dissolved. Then, dianhydride monomer 3,3′,4,4′-biphenyltetracarboxylic dianhydride (7.3600 g, 0.025 mol) was added and reacted for 12 hours to obtain a high-viscosity polyamic acid (PAA) solution.

[0148] (2) The polyamic acid organic solution (2.00 g, 5 wt%) obtained in step (1) and the carbon nanotube organic solvent dispersion modified by polyvinyl pyrrolidone are mixed evenly and diluted to a solid content of 3 wt%.

[0149] (3) The polyamic acid / carbon nanotube organic solvent dispersion obtained in step (2) was cast onto a glass plate with a size of 5×10 cm. Finally, the polyamic acid / polyvinyl pyrrolidone / carbon nanotube composite film was obtained by heat treatment in an oven at 50° C., 60° C., 70° C., and 80° C. for 2 h, 2 h, 2 h, and 2 h, respectively.

[0150] (4) The process is the same as step (4) in Example 1.

[0151] In this comparative example, the polyimide / carbon nanotube composite electromagnetic shielding film prepared based on the organic solvent system has significantly deteriorated mechanical properties when the carbon nanotube content is 50wt%, and the tensile strength can only reach 67MPa, which is much lower than the 212MPa of the water-based polyimide / carbon nanotube composite film obtained with the same carbon nanotube content (50wt%). When the thickness of the composite film is ~0.035mm, the corresponding electromagnetic shielding performance can reach 24.8dB, which is lower than the 26.3dB of the water-based polyimide / carbon nanotube composite film.

[0152] Comparative Example 3

[0153] (1) The process is the same as step (1) in Example 1.

[0154] (2) The process is the same as step (2) in Example 1.

[0155] (3) The polyamic acid salt aqueous solution (4.00 g, 5 wt%) and carbon nanotube powder (0.20 g, 0.20 g) obtained in step (2) were added to 9.10 g of deionized water to prepare a uniform mixed dispersion with a solid content of 3 wt%, and the above dispersion was poured onto a glass plate with a size of 5x10 cm. Finally, the polyamic acid salt / carbon nanotube composite film was obtained by heat treatment at 50°C, 60°C, 70°C, and 80°C in an oven for 2 h, 2 h, 2 h, and 2 h, respectively.

[0156] (4) The process is the same as step (4) in Example 1.

[0157] (5) The mechanical properties of the water-based polyimide / carbon nanotube composite film prepared directly from polyamic acid salt and carbon nanotube powder decreased when the carbon nanotube content was 50wt%, and the tensile strength was only 151MPa, and the corresponding elastic modulus was 6.3GPa. When the thickness of the composite film was 0.032mm, the corresponding electromagnetic shielding performance could reach about 23dB, which can also meet the needs of commercial applications (>20dB). However, at the same carbon nanotube content (50wt%), compared with the tensile strength of 212MPa of the PVP-modified composite film, the mechanical properties decreased significantly, and the electromagnetic shielding effectiveness decreased by about 3.3dB.

[0158] Comparative Example 4

[0159] (1) The process is the same as step (1) in Example 1.

[0160] (2) The process is the same as step (2) in Example 1.

[0161] (3) The process is the same as step (3) in Example 1.

[0162] The water-based polyamic acid salt / carbon nanotube composite electromagnetic shielding film prepared in this comparative example has poor mechanical properties when the carbon nanotube content is 9.1wt% (the mass ratio of polyamic acid salt to carbon nanotube is 10:1), and the tensile strength can only reach 32MPa. However, the average tensile strength of the composite film after cyclization can reach 284MPa, indicating that the lack of imidization has a great influence on the mechanical properties of the composite film.

[0163] Comparative Example 5

[0164] (1) Add polyvinyl pyrrolidone / carbon nanotube aqueous dispersion (4.00 g, 5 wt%) to 2.67 g of deionized water and disperse evenly to prepare a carbon nanotube dispersion with a solid content of 3 wt%, and an average particle size of the dispersion is 313 nm. The above dispersion is cast on a glass plate with a size of 5x10 cm. Finally, heat-treat in an oven at 50°C, 60°C, 70°C, and 80°C for 2 h, 2 h, 2 h, and 2 h, respectively, to obtain a polyvinyl pyrrolidone / carbon nanotube composite film.

[0165] (2) The polyvinyl pyrrolidone / carbon nanotube composite film obtained in the above step (3) is treated at 100°C, 150°C, 200°C, 250°C, 300°C and 350°C for 1h, 1h, 1h, 0.5h and 0.5h respectively to obtain a carbon nanotube composite film.

[0166] (3) The carbon nanotube film finally prepared is extremely brittle, and the mechanical properties drop sharply, with a tensile strength of only 30 MPa. Figure 4 As shown, it cannot meet the needs of practical applications.

[0167] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0168] Obviously, the embodiments of the present invention shown above are only intended to illustrate the principles of the present invention, rather than to limit its implementation. Those skilled in the art can make other forms of modifications or changes to the present invention based on the above description. Since it is impossible to list all implementations in detail, any obviously derivable technical solution changes are still protected by the present invention.

Claims

1. A method for preparing a high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film, characterized in that: include: reacting a first mixed reaction system comprising a diamine monomer, a salt-forming agent and a dianhydride monomer to obtain an aqueous polyamic acid salt; The polyvinyl pyrrolidone-modified carbon nanotube aqueous dispersion and aqueous polyamic acid salt are uniformly mixed to form an aqueous polyamic acid salt / carbon nanotube dispersion; The aqueous polyamic acid salt / carbon nanotube dispersion is applied to a substrate, and then subjected to thermal imidization treatment to obtain a high-performance aqueous polyimide / carbon nanotube composite electromagnetic shielding film.

2. The preparation method according to claim 1, characterized in that: The diamine monomer includes Any one or a combination of two or more.

3. The preparation method according to claim 1, characterized in that: The dianhydride monomer is 4. The preparation method according to claim 1, characterized in that: The salt-forming reagent includes Any one or a combination of two or more.

5. The preparation method according to claim 1, characterized in that: The molar ratio of the diamine monomer to the dianhydride monomer is 0.98:1 to 1:1; and / or the molar ratio of the dianhydride monomer to the salt-forming agent is 1:2N1:

5.

6. The preparation method according to claim 1, characterized in that: include: The diamine monomer and deoxygenated water are mixed, and a salt-forming reagent is added to assist the diamine monomer to dissolve quickly, and then the dianhydride monomer is added and stirred and mixed evenly, and reacted to obtain an aqueous polyamic acid salt solution; preferably, the stirring speed is 100-300 rpm; preferably, the ratio of the diamine monomer to water is (0.01-0.05) mol: (50-200) mL; preferably, the viscosity of the aqueous polyamic acid salt solution is 40000-100000 cP; And / or, the reaction is carried out under a protective atmosphere, the reaction temperature is 25 to 80° C., and the reaction time is 6 to 12 hours.

7. The preparation method according to claim 1, characterized in that: include: Modifying carbon nanotubes with polyvinyl pyrrolidone to obtain a polyvinyl pyrrolidone-modified carbon nanotube aqueous dispersion; And / or, the preparation method comprises: mixing the polyvinyl pyrrolidone-modified carbon nanotube aqueous dispersion and aqueous polyamic acid salt, ultrasonicating and stirring to obtain a uniformly mixed aqueous polyamic acid salt / carbon nanotube dispersion.

8. The preparation method according to claim 7, characterized in that: The diameter of the carbon nanotubes is 5 to 50 nm; and / or the mass ratio of the polyvinyl pyrrolidone to the carbon nanotubes is 1:4 to 1:9; And / or, the mass ratio of the aqueous polyamic acid salt to the carbon nanotubes is 10:1N1:5; and / or, the solid content of the aqueous polyamic acid salt / carbon nanotube dispersion is 20 to 60 mg / mL, preferably 20 to 50 mg / mL; And / or, the temperature of the ultrasound is 20-30° C., the time of the ultrasound is 0.5-2 h, and the power of the ultrasound is 100-500 kHz; And / or, the stirring speed is 300-600 rpm, and the stirring time is 12-36 hours; And / or, the process conditions of the thermal imidization treatment include: heating treatment at a gradient temperature of 100 to 450° C. for 0.5 to 2 h under nitrogen or vacuum conditions.

9. The preparation method according to claim 8, characterized in that: include: Casting the aqueous polyamic acid salt / carbon nanotube dispersion on a substrate, and heating to remove the solvent to obtain an aqueous polyamic acid salt / carbon nanotube composite film; The water-based polyamic acid salt / carbon nanotube composite film is heated to complete thermal imidization treatment and remove polyvinyl pyrrolidone to obtain a high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film; Preferably, the heating temperature is 50-80°C and the heating time is 1-3h; and / or, the substrate comprises a glass plate; And / or, the process conditions of the thermal imidization treatment include: first heating to 100-120°C and keeping for 1-2h, heating to 150-170°C and keeping for 1-2h, heating to 200-220°C and keeping for 1-2h, heating to 250-270°C and keeping for 1-2h, heating to 300-320°C and keeping for 0.5-2h, and finally heating to 350-450°C to dehydrate the polyamic acid to form an imide ring, and performing the cyclization treatment for 0.5-2h.

10. A high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film prepared by the preparation method described in any one of claims 1 to 9; preferably, the high-performance water-based polyimide / carbon nanotube composite electromagnetic shielding film has a thickness of 20 to 350 μm, a tensile strength of 68 to 284 MPa, and a maximum electromagnetic shielding effectiveness of 51 dB.

Citation Information

Patent Citations

  • Method for preparing polyimide / carbon nanotube nanocomposite

    CN102702744A

  • Aqueous polyimide precursor solution composition and method for producing aqueous polyimide precursor solution composition

    CN103097463A

  • High-dielectric-constant polyimide film provided with multiwalled carbon nanotubes and preparation method of high-dielectric-constant polyimide film

    CN104448312A

  • Polyimide barrier thin film material, preparation method and application thereof

    CN110938305A

  • Preparation method of polyimide film with high elongation at break

    CN112961348A

Cited By

  • High-temperature-resistant water-based sizing agent as well as preparation method and application thereof

    CN122103571A